Isolasi dan Identifikasi Bakteri Asam Laktat dari Bekasam Ikan Nilem (Osteochilus hasselti) sebagai Produk Fermentasi Lokal Muaro Jambi - Tiara Nabilah Putri; Ardi Mustakim (International Forum of Researchers and Lecturers, 2025)
This study was conducted to isolate and identify lactic acid bacteria (LAB) present in nilem fish bekasam, a traditional fermented product from Muaro Jambi. A 1-gram sample of bekasam, which had been fermented for 7 days, was used as the test material. The sample was diluted in stages to 10⁻⁶ and then plated on Nutrient Agar medium using the pour plate method. The incubation was carried out at 37°C for 24-48 hours. Upon observation, bacterial colonies with characteristics typical of lactic acid bacteria were noted. These colonies were small in size, round in shape, white to cream in color, had smooth surfaces, and flat edges. Gram staining tests revealed that most isolates were Gram-positive bacteria with rod or oval shapes, which is consistent with the characteristics of the Lactobacillus genus. Further tests showed that these bacteria were catalase-negative, non-spore-forming, and produced lactic acid as their primary metabolic product. These findings suggest that lactic acid bacteria, particularly the Lactobacillus species, dominate the microbial population in the fermentation process of nilem fish bekasam. The study highlights the significant role of LAB, especially Lactobacillus, in the fermentation process, contributing to the unique flavors, texture, and preservation properties of this traditional fermented product. This research emphasizes the importance of LAB in traditional food fermentation processes.